Evolution of lasR mutants in polymorphic Pseudomonas aeruginosa populations facilitates chronic infection of the lung - Kelei Zhao; Xiting Yang; Qianglin Zeng; Yige Zhang; Heyue Li; Chaochao Yan; Jing Shirley Li; Huan Liu; Liangming Du; Yi Wu; Gui Huang; Ting Huang; et al. (Nature Communications, 2023)
Abstract Chronic infection with the bacterial pathogen Pseudomonas aeruginosa often leads to coexistence of heterogeneous populations carrying diverse mutations. In particular, loss-of-function mutations affecting the quorum-sensing regulator LasR are often found in bacteria isolated from patients with lung chronic infection and cystic fibrosis. Here, we study the evolutionary dynamics of polymorphic P. aeruginosa populations using isolates longitudinally collected from patients with chronic obstructive pulmonary disease (COPD). We find that isolates deficient in production of different sharable extracellular products are sequentially selected in COPD airways, and lasR mutants appear to be selected first due to their quorum-sensing defects. Polymorphic populations including lasR mutants display survival advantages in animal models of infection and modulate immune responses. Our study sheds light on the multistage evolution of P. aeruginosa populations during their adaptation to host lungs.